Carbon Nanobelts: Brief History and Perspective - Imoto, Daiki; Yagi, Akiko; Itami, Kenichiro (Precision Chemistry, 2023)
Carbon nanotubes (CNTs) are an emerging nanomaterial because of their outstanding performance in various applications. In recent years, the segment molecules of CNTs, referred to as carbon nanorings (CNRs) or carbon nanobelts (CNBs), have gained attention for their unique structures and properties, as well as their potential as seed molecules for the precise synthesis of CNTs. CNBs are rigid and thick segments of CNTs whose synthesis has been addressed by scientists fascinated by the uniqueness of CNBs long before the discovery of CNTs. After 60 years of efforts by synthetic chemists all over the world, the synthesis of the first CNB, (6,6)CNB, was achieved by our group in 2017. Since this milestone, diverse types of nanobelts have been synthesized through various synthetic routes, thereby demonstrating their photophysical, magnetic, and redox properties derived from rigid belt structures. The applications of CNBs have also been introduced recently. The formation of the host–guest complex, transformation to three-dimensional molecules, and measurement of conductivity have been reported for CNBs. This paper summarizes the brief history and perspective of CNBs. Further synthetic campaigns and aggressive application of CNBs would create novel and groundbreaking scenes in materials science.